Deoxycholic Acid Upregulates Serum Golgi Protein 73 through Activating NF-κB Pathway and Destroying Golgi Structure in Liver Disease - Danli Yang; Mingjie Yao; Ying Yan; Yanna Liu; Xiajie Wen; Xiangmei Chen; Fengmin Lu (Biomolecules, 2021)
Golgi protein 73 (GP73) is upregulated in a variety of liver diseases, yet the detailed mechanism is poorly characterized. We analyzed GP73 in a retrospective cohort including 4211 patients with chronic liver disease (CLD) or hepatocellular carcinoma (HCC). The effect of deoxycholic acid (DCA) and nuclear factor-kappa B (NF-κB) on expression and release of GP73 in Huh-7 and SMMC7721 cells were studied. A mouse study was used to confirm our findings in vivo. A positive correlation was found between serum GP73 and total bile acid (TBA) in cirrhotic patients (r = 0.540, p < 0.001), higher than that in non-cirrhotic CLD (r = 0.318, p < 0.001) and HCC (r = 0.353, p < 0.001) patients. In Huh-7 and SMMC7721 cells, DCA upregulated the expression and release of GP73 in a dose- and time-dependent manner. After overexpressing NF-κB p65, the promoter activity, GP73 messenger RNA (mRNA) level, and supernatant GP73 level were increased. The promotion effect of DCA on GP73 release was attenuated after inhibiting the NF-κB pathway. Mutating the binding sites of NF-κB in the sequence of the GP73 promoter led to a declined promoting effect of DCA on GP73. The upregulation role of DCA in GP73 expression through the NF-κB pathway was confirmed in vivo. In addition, exposure to DCA caused disassembly of Golgi apparatus. In summary, DCA upregulates the expression and release of GP73 via activating the NF-κB pathway and destroying the Golgi structure.